From Central Asia to Kashmir: A Holistic View of Mysticism - Altaf Hussain Yatoo (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2021)
Persian spirituality exerted a profound influence on the religious culture of Kashmir. The local Hindu Shaivite monism that went back to the ninth century was propagated by the Rishi ascetics. This paper aims to examine the influence of Sufism on the popular Islamic culture in Kashmir, in particular the role of the fourteenth-century figure of Nund Rishi or Shaykh Nūruddīn. The findings will be based on the qualitative analysis of the historical sources pertaining to the period concerned, with a focus on the Sanskrit epic of Rajatarangini and the poetry of Nund Rishi which explicitly refers to famous Persian mystics. This study has valid implications for the research on the causes of the socio-cultural transformation of Kashmir that were not only initiated but also taken to its completion and fruition by the local Rishi order.